MODIFICATION OF ALTERNATING CURRENT GENERATOR SYSTEM SIMULATOR: ANALYSIS USING BRUSHLESS DIRECT CURRENT MODULE (xxxx-xxxx, 2025)
This study aims to design and test a simulator of the alternating current generator starter system using a step-up dc to dc converter and a brushless direct current controller as an instructional medium. The simulator is developed to help learners understand the working principle of the alternating current generator starter system, which integrates the functions of both a starter and an alternator into a single unit. The research method employed is a technical and experimental approach, which includes needs analysis, component selection, assembly, and both electrical and mechanical testing. Testing was carried out to ensure the functionality of each part, such as increasing the voltage from 12V to 36V and regulating current through the brushless direct current controller to rotate the rotor. The results indicate that the simulator accurately replicates the operational characteristics of the alternating current generator starter system, including the relationships between voltage, current, rotor speed, and back electromotive force. Electrical stability and the simulator frame ensure the simulation runs smoothly without mechanical disruption, making it appropriate for educational and technical training purposes and offering potential for further development. Penelitian ini bertujuan untuk merancang dan menguji simulator sistem starter alternating current generator menggunakan step-up dc to dc converter dan controller brushless direct current sebagai media pembelajaran. Simulator dirancang untuk membantu memahami prinsip kerja sistem starter alternating current generator yang menggabungkan fungsi starter dan alternator dalam satu unit. Metode penelitian menggunakan pendekatan teknis dan eksperimental yang meliputi analisis kebutuhan, pemilihan komponen, perakitan, dan pengujian kelistrikan serta mekanis. Pengujian dilakukan untuk memastikan fungsi setiap bagian, termasuk peningkatan tegangan dari 12V menjadi 36V dan pengaturan arus oleh controller brushless direct current untuk memutar rotor. Hasil penelitian menunjukkan bahwa simulator dapat mereplikasi karakteristik operasional sistem starter alternating current generator secara akurat, termasuk hubungan antara tegangan, arus, kecepatan rotor, dan back electromotive force. Stabilitas kelistrikan dan rangka simulator memastikan simulasi berjalan sesuai rancangan tanpa gangguan mekanis, sehingga simulator ini layak digunakan untuk pembelajaran dan pelatihan teknis serta berpotensi dikembangkan lebih lanjut.